The prophet yusuf and the kings dream: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story tells of Prophet Yusuf, who interprets the king's troubling dream about seven fat cows and seven lean ones. His wisdom not only saves the kingdom from famine but also showcases themes of patience, trust in God, and the importance of using one's gifts to help others.